Day-to-Day Variability of Walking Performance Measures in Individuals Poststroke and Individuals With Parkinson Disease. Issue 4 (October 2020) - Holleran, Carey L.; Bland, Marghuretta D.; Reisman, Darcy S.; Ellis, Terry D.; Earhart, Gammon M.; Lang, Catherine E.
Abstract : Background and Purpose: Improvement of walking performance is a primary goal for individuals poststroke or with Parkinson disease (PD) who receive physical therapy. More data about day-to-day variability of walking performance are critical for determining if changes in performance have occurred. Methods: Baseline assessments were utilized from an ongoing, observational, prospective cohort study including 84 individuals poststroke (n = 37) or with PD (n = 47) receiving outpatient physical therapy services to improve mobility. Participants wore step activity monitors for up to 7 days to measure walking performance (steps per day, walking duration, maximum 30-minute output, and peak activity index) in daily life. Correlation analyses evaluated relationships between both capacity and performance measures as well as the relationships between mean performance variables and day-to-day variability. Regression analyses explored factors that contribute to variability in day-to-day performance variables. Results: Mean steps per day for participants poststroke (5376 ± 2804) and with PD (8149 ± 4490) were consistent with previously reported cohorts. Greater amounts of walking were related to more day-to-day variability, with moderate correlations found between the mean and day-to-day variability of each performance measure, regardless of medical diagnosis or walking speed. Day-to-day variability is large (upwards of 50% of the mean), with the amount of walking performance serving as the primary predictor of day-to-day variability in walking performance. Discussion and Conclusions: The results of this study elucidate the factors that are related to and predict day-to-day variability of performance. Walking performance metrics should be evaluated over multiple days and greater variability should be anticipated with greater amounts of performance. Video Abstract available for more insights from the authors (see the Video, Supplemental Digital Content 1, available at: http://links.lww.com/JNPT/A319 ). Abstract : Supplemental Digital Content is Available in the Text.